Mode 3 Knowledge Production in Quadruple Helix Innovation Systems 21st-Century Democracy, Innovation, and Entrepreneurship for Development - Carayannis, Elias G.; Campbell, David F.J.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
None
Keywords: Economics; Economics/Management Science; Business/Management Science, general